Highly Ordered TiO2 Nanotubes for Electrochemical Sensing of Hair Dye Basic Brown 17 - Oliveira, R. A. G. de [UNESP]; Zanoni, M. V. B. [UNESP] (Wiley-Blackwell, 2013)
Self-organized Ti/TiO2 nanotubular array electrodes were prepared by electrochemical anodization and used to monitor the reduction of the hair dye basic brown 17 (BB17) at a potential of -0.60V vs. Ag/AgCl. Analytical curves were obtained from 1.0x10(-6) to 8.0x10(-5)molL(-1) with a detection limit of 1.3x10(-7)molL(-1) by using the best experimental conditions, linear scan voltammetry at pH6, scan rate=60mVs(-1), and accumulation time=5min. The detection system performance was not interfered by other hair dyes and successfully used to determine the dye in tap water samples.
Keywords: Ti; TiO2 nanotube electrode; Hair dye; Temporary dyes determination; Adsorption of dye on TiO2 nanoarrays